Challenges for crop diversification in cotton-based farming systems in India: a comprehensive gap analysis between practices and policies - Keller, Chigusa; Joshi, Smita; Joshi, Tanay; Goldmann, Eva; Riar, Amritbir (Frontiers in Agronomy, 2024)
Crop diversification is a promising practice to improve the sustainability of agricultural production systems, contributing to biodiversity conservation, ecosystem functions, and food security without compromising productivity. Although diverse cropping systems may be more labour-intensive and require good knowledge of the specific cropping system in the local context, they have high potential in managing many of the problems faced in current cotton production in India. However, the adoption of crop diversification is still moderate, with an overall crop diversification index (CDI) of 0.65 for all of India and state-wise CDI between 0.43 and 0.83. Therefore, a four-phased study was conducted to identify the main barriers to crop diversification in cotton-based farming systems in India and highlight levers that can foster their wide adoption to improve the livelihoods of smallholder farmers. The study was carried out between January to October 2020 and consisted of i) a literature review of regional and national policy and planning, ii) situational analysis with a problem tree approach, iii) individual stakeholder interviews with stakeholders from the broader Indian cotton sector, and iv) a participatory feedback workshop with said stakeholders. A total of 51 stakeholders from 24 different organizations were interviewed, 37 of them on technical aspects of crop diversification and 21 stakeholders on market and policy aspects. The same stakeholders were invited to the participatory feedback workshop, where 26 participated in the session on different benefits of crop diversification practices, and the session on market and policy challenges counted 24 participants. The study focused on the main organic cotton producing states in India: Gujarat, Madhya Pradesh, Maharashtra, Haryana, Odisha, and Andhra Pradesh. In our study, it became evident that many policies and governmental schemes exist to promote national food security, sustainable agriculture, and agricultural marketing infrastructure, but crop diversification is still not gaining momentum on the ground. Various levers were identified in the areas of market and procurement, capacity building and knowledge transfer, supply industry and infrastructure, and farmers and women empowerment, where the current policy landscape is failing to foster crop diversification effectively on the farm level.